Lack of polymorphism suggests a recent bottleneck of Aloidendron pillansii: Exploration into the population of Aloidendron pillansii from phylogeographical analysis of molecular data - Josephs, Randall Evan (Department of Biological Sciences, 2015)
Includes bibliographical references.